The use of hedging devices in applied linguistics academic discourse: The case of Reading in a foreign language and English language teaching research articles - Nguyen, Tuan Anh (H. : ĐHQGHN, 2018)
Hedging enables academic writers to mitigate claims and minimize the impositions that may be found in such claims (Hyland, 1996). Although the literature has had vast research on hedging in research articles, not much has been known about the difference or similarity among journals in one feld in the use of hedging devices. Using the document analysis method, the present study aims to make a comparative analysis of hedging in two linguistics research journals, namely Reading in a Foreign Language (RFL) and English Language Teaching (ELT), in order to investigate what hedging forms and functions are most frequently used in RFL and ELT, and how hedging forms and functions are distributed in the Introduction, Results, Discussions and Conclusions sections in the two journals. Based on the data analyzed, it was found that RFL and ELT research article writers tend to have the same preference for the use of different hedging forms for different equivalent purposes and functions. This similar hedging pattern is believed to be of value to those who are trained as academic writers in the feld of linguistics